EFFECT OF GULZOR BALM ON THE IMMUNE RESPONSE IN IRRADIATED ANIMALS WITH DIFFERENT ACETYLATION TYPES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Recent advances in clinical sciences, particularly immunology, indicate that the pathogenesis of many diseases is, to varying degrees, associated with immune system dysfunction. Despite significant progress in the development of synthetic drugs, there remains a strong interest in plant-based remedies and their active components with immunotropic properties, especially for the treatment of chronic and long-term illnesses. Herbal immunomodulators serve as alternative therapeutic agents for various diseases, particularly in cases of weakened immune responses or selective immunosuppression, such as autoimmune syndromes.